Seguimento do recém-nascido prematuro: um desafio para as ações de promoção de saúde na atenção básica - Lopes, Domitila Natividade Figueiredo (2012)
The aim of this study was to analyze the following premature newborns (PN) in an outpatient clinic specifically for this clientele, a municipality in the state of Sao Paulo, This is a descriptive study based on data obtained from medical records of 89 preterm infants enrolled and followed up at outpatient clinics and data obtained by interviewing the mothers. From the data related to PN, it was observed that 47.2% were female and 52.8% male; most with gestational age 23-31 weeks, weighing 1000 to 1500 grams and 71.9% were born cesarean section. The data pointed to most maternal primiparous, 13.0% aged between 15 and 19 years and 10.9% over 36 years, marital status stable, well-educated, family income between one and five minimum wages. It was found that 98.9% received prenatal care, usually beginning in the first quarter. The risk factors for maternal and fetal prematurity highlighted the occurrence of urinary tract infection, preeclampsia, twin pregnancy, premature rupture of membranes, congenital anomalies, fetal distress, oligohydramnios and poliidramnio. The sample surveyed, 53.9% had some type of perinatal complication, the most observed: severe jaundice, 45.8% and hypoxia or anoxia, 33.3%. Referring to the Apgar score, 47.2% of preterm infants had an index lower than in the first seven minutes of life, 21.4% continued with less than seven at five minutes. In relation to postnatal complications observed a significant number of sepsis, bronchopulmonary dysplasia and respiratory distress syndrome of the newborn. The largest number of preterm infants, 52.8% remained hospitalized for seven to 29 days in the Neonatal Intensive Care Unit (NICU) and neonatal nursery (BN) during hospitalization and underwent several procedures necessary for its survival, among them: ventilation, parenteral nutrition and medication (antibiotics and surfactant). Regarding the follow-up results showed that the total sample, 52.8% were followed up between 13 and 22 months and were aged between 15 and 24 months, with a periodicity of monthly visits, indicating adequate monitoring, and 95.5% were referred for evaluation by specialists. Although the results obtained from the interviews with the mothers have demonstrated a significant level of satisfaction related to care and advice they had received outpatient follow-up of preterm infants is still a challenge for health managers and a multidisciplinary team in primary care, since they demand engagement technical training and continuous development of actions to promote health for these patients vulnerable to complications in the short and long term.